Densidade de árvores por diâmetro na Floresta Estacional Decidual no Rio do Grande Sul - Meyer, Evandro Alcir (2011)
The objective of the work was to study the relationship between the density of trees per hectare and the average diameter to a Deciduous Forest, as well as adjust the model to describe this behavior Reineke. The study area is located in the town of Silveira Martins, in the central region of Rio Grande do Sul and is in early stages of succession after agriculture. The information about the number of the trees per hectare and the average diameter were obtained by the method of density-off proposed by Spurr. These plots were sampled in the early stages of a secondary forest, picking up areas where the predominant Camboatá-vermelho (Cupania vernalis). As natural forests have irregular spacing, density is highly variable, therefore, to select only high-density plots were chosen in areas that there was the occurrence of dead individuals. Were tested different methods to estimate the upper limit of the self thinning line: regression analysis (for all data and relative density greater than 60%), correcting the intercept so that the wastes were negative, the manual adjustment, the relative density (DR> 90%) and stochastic frontier analysis. The method that estimated the maximum density was regression analysis with data from at least 60% of maximum density, obtaining a slope of -1.563 for the model of Reineke. There was no significant difference between the powers provided by the different methods. The maximum Stand Density Index was 1779 trees per hectare, to a dg of 25 cm. The density management diagram was constructed on the basis of basal area, number of trees per hectare and diameter of the tree of average basal area. Were used the densities of 15% and 60%, to close the canopy, and the induction of mortality, respectively. The densities were determined proportionally to the maximum density by stand density index (PDI) for a reference diameter of 25 cm in different classes of index 200, since the IDP 1700, to a minimum of 300. Populations whose density is greater than 60% of the maximum were considered overstocked, between 60 and 15% fully stocked, and below 15% under stocked. They recommended a combination of Dendrogram generated in this study with the method of Spurr to guide interventions in the Deciduous Forest.